New approaches to the synthesis of benzo[h]pyrroloisoquinoline derivatives. Issue 48 (28th November 2019) - Ershova, Anastasia A.; Zinoveva, Anna D.; Borisova, Tatiana N.; Titov, Alexander A.; Varlamov, Alexey V.; Voskressensky, Leonid G.; Tuyen Nguyen, Van; Anh Le, Tuan
Graphical abstract: Highlights: A novel approach to the synthesis of the previously inaccessible compounds. The structure of the compounds ensured with single X-ray crystal analysis. The process can be described as one-pot domino reaction. A number of hydrogenated benzo[ h ]pyrrolo[2, 1- a ]isoquinoline derivatives have been obtained in yields close to 90%. Abstract: An effective strategy for the synthesis of benzo[ h ]pyrrolo[2, 1- a ]isoquinoline derivatives has been developed. The process can be described as a one-pot domino reaction that consists of an initial Michael addition, intramolecular cyclization, and subsequent transformations leading to the formation of the desired products. A wide range of structurally diverse hydrogenated benzo[ h ]pyrrolo[2, 1- a ]isoquinolines were obtained in 34–98% yield. This strategy represents an efficient catalyst-free procedure that allows the synthesis of previously inaccessible compounds.